2020
DOI: 10.1186/s12906-020-2861-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and prognosis of upper tract urothelial carcinoma complicated with aristolochic acid nephropathy after radical nephroureterectomy

Abstract: Background The purpose of this study was to identify the clinicopathologic characteristics and prognosis of upper tract urothelial carcinoma (UTUC) patients complicated with aristolochic acid nephropathy(AAN) after radical nephroureterectomy (RNU). Methods The clinical data of 42 UTUC patients with AAN (AAN group) and 238 UTUC patients without AAN (Non-AAN group) were retrospectively reviewed. All patients received a RNU with excision of bladder cuff. Demographic and clinical data, including preoperative ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…73 Our subgroup analysis showed that AA exposure was associated with 1.949-fold increased risk of intravesical recurrence of UTUC, and 1.477-fold increased risk in patients diagnosed with AAN. It is worth noting that among the three studies reporting contralateral UTUC recurrence, 49,53,56 the recurrence rates of 0-5% in the control groups were similar to that of 2-6% in the general population. However, the rates in the AA groups were very high (13.75-25%), 49,53,56 which contributed to an overall 3.760-fold increased risk.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…73 Our subgroup analysis showed that AA exposure was associated with 1.949-fold increased risk of intravesical recurrence of UTUC, and 1.477-fold increased risk in patients diagnosed with AAN. It is worth noting that among the three studies reporting contralateral UTUC recurrence, 49,53,56 the recurrence rates of 0-5% in the control groups were similar to that of 2-6% in the general population. However, the rates in the AA groups were very high (13.75-25%), 49,53,56 which contributed to an overall 3.760-fold increased risk.…”
Section: Discussionmentioning
confidence: 52%
“…One study investigating AA-RCC 23 was excluded because the aim of the study was to find the etiology of RCC in BEN regions. Seventeen studies reporting the risk 35,37,[40][41][42][43][44][45][46][47] or oncologic outcomes 44,48,50,51,[53][54][55][56] of AA-UTC, six studies reporting the molecular alterations in AA-UTUC 57,[63][64][65] or AA-RCC, 22,60 and one study reporting both the risk and molecular alterations in AA-UTUC 68 were newly retrieved in the present systematic review.…”
Section: Comparison Of the Included Studies Between The Present And Previous Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of AAs can lead to a rapid renal toxicity and, at certain levels, to liver (Ng et al, 2017;Lu et al, 2020) and kidney cancer (Vanherweghem et al, 1993;Debelle et al, 2008). Consumption of AAs-containing herbal remedies in South Asia remains a cause of serious concern for public health to date (Lu et al, 2020;Shan et al, 2020). Certain cases in Europe also have been registered in 1992; when several female patients in Belgium, after taking two Chinese herbs (Stephania tetrandra and Magnolia officinalis), as slimming treatment, suffered from rapidly progressive interstitial nephritis (Vanherweghem et al, 1993).…”
Section: Aristolochic Acids and Their Association With Genotoxicity Amentioning
confidence: 99%